Credit chains and the propagation of financial distress - Frédéric Boissay (European Central Bank (ECB), 2006)
The purpose of this paper is to analyze how shocks propagate through a network of firms that borrow from, and lend to, each other in a trade credit chain, and to quantify the effects of financial contagion across firms. I develop a theoretical model of financial contagion, in which the default of one firm may cause a chain reaction such that its creditors also get into financial difficulties, even though they are sound in the first place. I calibrate and simulate the model using US annual data over the period 1986-2004. At the microeconomic level, I find that, when customers of a sound firm are financially distressed, then this firm gets into financial difficulties with probability that ranges from 4.1% to 12.8% (depending on the business cycle and the underlying economic scenario). Looking at the macroeconomic level, I find that defaults on trade debts lower aggregate GDP by at least 0.4%. During the second half of the 90's, these deadweight losses doubled and reached a high of 0.9% to 2.3% of GDP (depending on the underlying economic scenario) before the recession of 2001. The results of the simulations also suggest that financial contagion across businesses had been 25% higher during the last recession than during the recession of the early 90's.
Keywords: E32; G29; G33; 330; business fluctuations; Financial contagion; trade credit; Lieferantenkredit; Geldpolitische Transmission; Konjunktur; USA